Battery active material, battery composite active material, and secondary battery

CN115668544BActive Publication Date: 2026-08-18PANASONIC ENERGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180038571.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-07
Filing Date
2021-06-03
Publication Date
2026-08-18
Estimated Expiration
2041-06-03

AI Technical Summary

Technical Problem

但是,锡系材料、硅材料在充放电时会引起活性物质的微粉化等,因此存在无法避免充放电容量降低的问题

Benefits of technology

[0028] A secondary battery containing a negative electrode with the active material of the present invention can maintain good initial coulombic efficiency and cycle characteristics, thereby increasing the discharge capacity to, for example, 800 mAh/g or more.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115668544B_ABST
    Figure CN115668544B_ABST
Patent Text Reader

Abstract

An object of the present application is to provide a battery active material capable of maintaining good initial coulombic efficiency and cycle characteristics and increasing discharge capacity to, for example, 800 mAh / g or more, a battery composite active material containing the battery active material, and a secondary battery containing these materials in a negative electrode. The battery active material of the present application is an amorphous silicon-based material composed of elements including Si, O, and C, and has a solid solution structure in which Si, O, and C are mixed at the atomic level. The battery active material of the present application is characterized by having a specific surface area of 0.1 m2 / g or more and less than 20 m2 / g, a pore volume of 0.01 cm3 / g or more and less than 0.5 cm3 / g, and a pore diameter of 2 nm or more and less than 20 nm. 29 The ratio (A / B) of the total value A of the integral values of the respective peaks attributed to SiO2C2 and SiO3C to the integral value B of the peak attributed to SiO4 in the range of chemical shifts 20 ppm to -150 ppm of the Si-NMR spectrum is 0.5 or more and 5.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an active material for batteries as an amorphous silicon-based material composed of elements including Si, O and C, a composite active material for batteries containing the active material for batteries, and a secondary battery containing these materials in the negative electrode. Background Technology

[0002] In recent years, with the widespread use of portable electronic devices such as smartphones, the demand for small, high-capacity rechargeable batteries has increased. Among these, the application of rechargeable batteries, such as lithium-ion batteries (sometimes referred to as LIBs), in electric vehicles (EVs) is rapidly expanding. For rechargeable batteries, the driving range (range) on a single charge is a crucial indicator of EV performance. The performance of the battery used in an EV is a key indicator of its capabilities, specifically high capacity, high efficiency, and high capacity retention.

[0003] In terms of charge / discharge capacity, tin (theoretical capacity: 994 mAh / g) and silicon (theoretical capacity: 4199 mAh / g) have higher theoretical capacities than existing types of carbon materials (graphite's theoretical capacity: 372 mAh / g), thus leading to extensive research. However, tin-based and silicon materials suffer from micronization of active materials during charge / discharge, resulting in an unavoidable decrease in charge / discharge capacity. Although many solutions have been proposed, none have been practically implemented, and improvements are ongoing.

[0004] On the other hand, it has been proposed that high-temperature sintered organosilicon compounds with direct silicon-carbon bonding can help improve capacity retention, as they are materials with lower capacity than silicon materials but less material degradation phenomena such as volume expansion during lithium storage due to side reaction behavior during charging and discharging (Patent Document 1 below).

[0005] In addition, for materials composed of silicon (Si), oxygen (O), and carbon (C), many schemes have been proposed for developing materials that maintain a certain charge-discharge capacity while achieving high capacity retention. Examples include: active materials using particles dispersed in a carbonaceous phase with a compositional formula SiOxCy (0.2≤x≤3, 1≤y≤5) (Patent Document 2 below); active materials obtained by sintering a crosslinked compound formed by curing reactive silanes or siloxanes with crosslinking groups at 700–1400°C under an inactive atmosphere (Patent Document 3 below); and active materials composed of silicon, carbon, and oxygen, with a carbon content of 0.2–10 mol%, an oxygen content of 0.5–40 mol%, and a Si-C bond percentage of 0.1–17.29 mol% or less relative to silicon atoms (Patent Document 4 below), etc.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 5-144474

[0009] Patent Document 2: Japanese Patent Application Publication No. 2003-197193

[0010] Patent Document 3: Japanese Patent Application Publication No. 2006-062949

[0011] Patent Document 4: Japanese Patent Application Publication No. 2009-283366 Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] However, among the active materials in the secondary batteries described in the aforementioned patent documents 1-4, there are no materials that can simultaneously improve charge / discharge capacity, initial coulombic efficiency (initial efficiency), and cycle characteristics (capacity retention characteristics). In particular, the estimated discharge capacity is less than 800 mAh / g, which is very low compared to silicon materials. This is a problem.

[0014] In view of the above-mentioned actual situation, the problem to be solved by the present invention is to provide a battery active material that can maintain good initial coulombic efficiency and cycle characteristics and increase the discharge capacity to, for example, 800 mAh / g or more, a battery composite active material containing the battery active material, and a secondary battery containing these materials in the negative electrode.

[0015] Methods for solving problems

[0016] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that by containing a battery active material with a specific microstructure in an amorphous silicon-based material composed of elements including Si, O and C, the above-mentioned problems can be solved, thus completing the present invention.

[0017] That is, the present invention is as follows.

[0018] Item 1. An active material for batteries, which is an amorphous silicon-based material composed of elements including Si, O, and C, in a solid state. 29 Within the chemical shift range of 20 ppm to -150 ppm in Si-NMR spectra, the ratio (A / B) of the total value A of the peak integrals attributable to SiO2C2 and SiO3C to the peak integral value B attributable to SiO4 is greater than 0.5 and less than 5.0.

[0019] Item 2. The active material for batteries as described in Item 1, wherein the starting temperature for reducing the weight of the active material during thermal decomposition in air is 550°C or higher.

[0020] Item 3. The active material for batteries as described in Item 1 or 2, wherein the weight reduction of the active material during thermal decomposition in air is 2 wt% or more and 30 wt% or less.

[0021] Item 4. The battery active material as described in any one of items 1 to 3, wherein, in the Raman spectrum of the active material, the value is located at 1595 cm⁻¹. -1 The nearby carbon G-band is located at 1320 cm⁻¹ -1 The peak intensity ratio (G / D) of the D band of nearby carbon is below 0.8.

[0022] Item 5. A secondary battery, wherein the negative electrode contains any one of items 1 to 4 of the active material.

[0023] Item 6. A composite active material for batteries, comprising, as a part of the constituent elements, any one of items 1 to 4, the active material.

[0024] Item 7. A composite active material for batteries, wherein the constituent elements of the composite active material described in Item 6 include at least one carbon material selected from graphite, low-crystallinity carbon, and amorphous carbon.

[0025] Item 8. A composite active material for batteries, comprising silicon particles with an average particle size of less than 150 nm in the constituent elements of the composite active material described in Item 6 or 7.

[0026] Item 9. A secondary battery, wherein the negative electrode contains any one of items 6 to 8, a composite active material.

[0027] Invention Effects

[0028] A secondary battery containing a negative electrode with the active material of the present invention can maintain good initial coulombic efficiency and cycle characteristics, thereby increasing the discharge capacity to, for example, 800 mAh / g or more. Attached Figure Description

[0029] Figure 1 It is the solid of the battery active material in Example 1. 29 Curve of Si-NMR spectrum. Detailed Implementation

[0030] <Active Materials for Batteries>

[0031] The battery active material of this invention is an amorphous silicon-based material composed of elements including Si, O, and C, with silicon carbide (SiOC) as the main component, and is composed of a three-dimensional network structure of Si, O, and C elements. Based on the type of atoms bonded to Si (O or C) and the number of bonds with each atom, it can be mainly divided into three types, denoted as SiO2C2, SiO3C, and SiO4, respectively. The substances formed by the further random bonding of Si with O and C in various ratios are called SiOC. The battery active material of this invention is in solid form. 29 Within the chemical shift range of 20 ppm to -150 ppm in Si-NMR spectra, the ratio (A / B) of the total value A of the peak integrals attributable to SiO2C2 and SiO3C to the peak integral value B attributable to SiO4 is greater than 0.5 and less than 5.0.

[0032] In the charging and discharging process of a lithium-ion secondary battery, taking the case where carbon is used as the negative electrode with active material as an example, during charging, carbon and lithium ions form chemical bonds through an insertion reaction, and carbon captures lithium. During discharging, the lithium captured by carbon releases electrons to become lithium ions and undergoes a release reaction to detach from carbon. By repeatedly carrying out this insertion and release reaction between carbon and lithium ions, the reaction can be reversibly carried out for charging and discharging. In the case of SiOC as the active material of the present invention, SiO2C2, SiO3C, and SiO4 are randomly combined to form an active material. SiO2C2 and SiO3C can reversibly undergo insertion and release reactions with lithium ions, but SiO4 will react with some lithium ions to form silicate compounds, so sometimes the insertion and release reactions of lithium ions are partially irreversible.

[0033] To elaborate further, the proximity of lithium ions causes a change in the internal electron distribution of SiOC, leading to electrostatic bonding and coordination bonds between SiOC and lithium ions. Therefore, lithium ions are stored within the SiOC framework. Furthermore, due to their low coordination bond energy, lithium ion deintercalation reactions are easily facilitated. That is, SiOC can reversibly undergo lithium ion insertion and deintercalation reactions during charging and discharging. Therefore, by understanding this mechanism, we found that the combined amount of SiO2C2 and SiO3C relative to the amount of SiO4 significantly contributes to improving reversible capacity; the higher this combined amount, the higher the reversible capacity and the better the initial coulombic efficiency.

[0034] On the other hand, when there is a large amount of SiO4, when electrostatic bonding and coordination bonds are formed between SiOC and lithium ions, a chemical reaction between SiO4 and lithium ions is likely to occur, producing lithium silicate compounds with high chemical stability. Therefore, some lithium ions are fixed in the aforementioned SiO4.

[0035] Therefore, based on the above mechanism, reducing the amount of SiO4 present can improve the reversible charge-discharge capacity of the aforementioned silicon material. However, as with SiO4, when all bonds to Si are O atoms, the chemical bond energy is higher compared to the case where even one Si-C bond exists. It is believed that even if lithium ions do not detach from SiO4, it still plays a role in maintaining the framework structure of the silicon material, making SiOC significantly contribute to improving the capacity retention rate of the active material. Therefore, SiO4 is an essential structure in the SiOC active material of this invention.

[0036] In other words, a higher total amount of SiO2C2 and SiO3C relative to the amount of SiO4 leads to an increase in reversible charge-discharge capacity, but if it is too high, it will hinder the improvement of cycle characteristics. Conversely, a lower total amount of SiO2C2 and SiO3C relative to the amount of SiO4 improves cycle characteristics, but if it is too low, it will hinder the improvement of reversible charge-discharge capacity. Because of these properties, the specific ratio of the total amount of SiO2C2 and SiO3C to the amount of SiO4, as described later, becomes an extremely important factor. Moreover, the individual amounts of SiO2C2, SiO3C, and SiO4 can be determined through solid... 29 Quantitative analysis was performed using Si-NMR measurements.

[0037] The structure of the amorphous silicon-based material of the present invention can be achieved through... 29 The material was identified by Si-solid-state NMR spectroscopy. The material is an active substance in its solid state. 29 In the Si-NMR spectrum, within the chemical shift range of 20 ppm to -150 ppm, the ratio (A / B) of the total integral value A of the peak values ​​attributed to SiO2C2 and SiO3C to the peak integral value B of SiO4 is in the range of 0.5 or higher and 5.0 or lower. The solid active material for batteries of the present invention... 29 An example of Si-NMR spectroscopy is shown. Figure 1 .

[0038] In the above solid 29 In Si-NMR spectra, such as Figure 1 As illustrated, the chemical shifts of the peaks attributed to SiO2C2, SiO3C, and SiO4 were observed approximately at -20 ppm to -50 ppm, -50 ppm to -90 ppm, and -90 ppm to -140 ppm, respectively. However, the chemical shifts of each peak vary depending on the surrounding environment of SiOC, therefore, the chemical shifts of the solid peaks need to be considered under various conditions. 29Si-NMR spectroscopy analysis revealed peaks belonging to SiO2C2, SiO3C, and SiO4, not necessarily within the aforementioned chemical shift range. By calculating the integral values ​​of the correctly assigned peaks based on the state of various samples and measurement conditions, the aforementioned ratio (A / B) can be determined. Solid 29 The integral values ​​in the Si-NMR spectrum represent the respective molar ratios of the amorphous silicon materials. Therefore, the ratio (A / B) mentioned above refers to the total molar ratio of SiO2C2 and SiO3C relative to 1 mole of SiO4. By keeping the ratio (A / B), i.e., the molar ratio, between 0.5 and 5.0, good initial coulombic efficiency and cycling characteristics can be maintained, thereby increasing the discharge capacity to, for example, 800 mAh / g or higher.

[0039] In addition, according to the above 29 In Si-solid-state NMR spectra, peaks for SiC4 and SiOC3 sometimes appear between 40 ppm and -20 ppm. Among the various peaks, SiC4 appears around 10 ppm to -20 ppm, and SiOC3 around 40 ppm to -20 ppm. This creates regions of peak repetition. 29 Si-solid-state NMR spectroscopy makes it difficult to accurately determine quantitative values. Furthermore, it is known that SiC4 does not undergo insertion / deintercalation reactions with lithium ions. Although SiOC3 does undergo insertion / deintercalation reactions with lithium ions, the amount is usually small. Ideally, it would be possible to define the range by adding the peak integral value of SiOC3 to the aforementioned total value A, and adding the peak integral value of SiC4 to the aforementioned total value B, etc., as a condition for improving charge / discharge characteristics. However, for the reasons mentioned above, considering the peak integral values ​​of SiC4 and SiOC3 is impractical. Therefore, as mentioned above, the ratio (A / B) of the total value A of the peak integral values ​​attributed to SiO2C2 and SiO3C to the peak integral value B attributed to SiO4 is specified to be in the range of 0.5 or higher and 5.0 or lower.

[0040] (Precursor)

[0041] The aforementioned SiOC can be formed by calcining a silane compound, which serves as a precursor to the SiOC, in an inert gas atmosphere. This silane compound has a molecular structure based on Si-O and Si-C bonds. By designing and adjusting the molecular structure of this precursor, the framework of the SiOC after high-temperature calcination in an inert gas atmosphere can be controlled, resulting in a SiOC framework closely related to the precursor's molecular structure.

[0042] The aforementioned precursor is preferably a molecular structure containing Si-O bonds and Si-C bonds, and more preferably, the Si-O bonds and Si-C bonds are in the same molecule.

[0043] For example, it is preferred to have structural units that include the following general formula (S-1) and / or the following general formula (S-2), and / or the following general formula (S-3), and / or the following general formula (S-4), and / or combinations of these following general formulas.

[0044] [Chemistry 1]

[0045]

[0046] [Chemistry 2]

[0047]

[0048] [Chemistry 3]

[0049]

[0050] [Chemistry 4]

[0051]

[0052] (In the above general formulas (S-1), (S-2), (S-3), and (S-4), R1, R2, R3, R4, R5, and R6 are all monovalent substituents. For example, each independently represents a hydrogen atom, hydroxyl group, hydrolyzable group, aliphatic hydrocarbon group, unsaturated hydrocarbon group, aromatic hydrocarbon, aralkyl group, acyl group, or a monovalent substituent having the following functional groups (vinyl, (meth)acrylate, amino, glycidyl, or thiol). X1, X2, X3, X4, X5, and X6 are all divalent substituents. Each independently represents an oxygen atom, alkylene group, alkene group, alkyne group, divalent aromatic group, ether group, ketone group, ester group, secondary amine group, amide group, or a divalent substituent formed by combining them. l, m, x, and y represent integers greater than 0.)

[0053] It should be noted that when there are multiple groups represented by symbols such as R1 and X1 in the above general formulas (S-1), (S-2), (S-3), and (S-4), they can be the same or different independently.

[0054] Examples of hydrolyzable groups include halogen atoms such as chlorine, bromine, and iodine; alkoxy groups such as methoxy, ethoxy, propoxy, butoxy, pentoxy, and hexanoyl; acyloxy groups such as phenoxy, naphthoxy, anthraceneoxy, pentoxy, allyloxy, iminooxy, alkenoxy, acyloxy, alkenoxy, amino, amide, aminooxy, and mercapto. Among these, methoxy and ethoxy are preferred.

[0055] By hydrolyzing these groups, the hydrolyzable silane groups form siloxane bonds through condensation reactions, or the unreacted portions remain unchanged or become hydroxyl groups. Solid polysiloxane compounds can be obtained by carrying out hydrolysis-condensation reactions between hydroxyl groups and unreacted hydrolyzable groups in parallel with the aforementioned thermosetting reaction.

[0056] Examples of aliphatic hydrocarbon groups mentioned above include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, neopentyl, tert-pentyl, 1-methylbutyl, 2-methylbutyl, 1,2-dimethylpropyl, 1-ethylpropyl, hexyl, isohexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 2,2-dimethylbutyl, 1-ethylbutyl, 1,1,2-trimethylpropyl, 1,2,2-trimethylpropyl, 1-ethyl-2-methylpropyl, 1-ethyl-1-methylpropyl, heptyl, octyl, decyl, dodecyl, myristyl, palmityl, stearyl, isostearyl, behenyl, and other straight-chain or branched alkyl groups with 1 to 30 carbon atoms. In addition, examples of cycloalkyl groups with 3 to 30 carbon atoms include cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl. Among these, methyl and ethyl are preferred as cycloalkyl groups.

[0057] As the aforementioned unsaturated hydrocarbon group, examples include vinyl, (meth)acryloyl, etc., which are alkenyl groups with 2 to 30 carbon atoms, such as vinyl, allyl, butenyl, etc., and monovalent substituents having functional groups as described later. Vinyl and allyl are preferred.

[0058] Examples of aromatic hydrocarbon groups include aryl groups with 6 to 30 carbon atoms, such as phenyl, tolyl, xylyl, naphthyl, styryl, 4-vinylphenyl, and 3-isopropylphenyl. Among these, phenyl is preferred as an aromatic hydrocarbon group.

[0059] Examples of aryl groups include benzyl, diphenylmethyl, and naphthylmethyl. Benzyl is preferred. Examples of acyl groups include aliphatic monocarboxylic acid acyl groups such as formyl, acetyl, propionyl, butyryl, valeryl, neovaleryl, lauroyl, myristyl, palmitoyl, and stearoyl, as well as acyl groups containing aromatic rings such as benzoyl and cinnamyl. Aliphatic monocarboxylic acid acyl groups are preferred, and acetyl is more preferred.

[0060] Examples of the functional groups among the aforementioned monovalent substituents with functional groups include vinyl, (meth)acryloyl, amino, glycidyl, and thiol groups. Specific examples include vinyltrialkoxysilane, (meth)acryloyloxypropyltrialkoxysilane, aminooxypropyltrialkoxysilane, glycidyloxypropyltrialkoxysilane, glycidyloxypropylmethyldialkoxysilane, epoxycyclohexyltrialkoxysilane, thiolpropyltrialkoxysilane, and p-styryltrialkoxysilane. Preferably, two or more of these functional groups are present in the polysiloxane segment; more preferably, 3 to 200 are present; and even more preferably, 3 to 50 are present. When two or more of these functional groups are present, the polysiloxane compound undergoes a crosslinking reaction by heating before thermal decomposition, forming a solid state, thereby facilitating easy thermal decomposition.

[0061] As described above, divalent substituents can include those having an oxygen atom, alkylene groups, alkynes, divalent aromatic groups, ethers, ketones, esters, secondary amines, and amides. Specific examples include alkylene groups such as methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, decylene, and cyclohexylene; alkynes such as vinylene, isoprene, butene, butadiene, pentene, hexene, heptene, octene, nonene, and decene; and alkynes such as acetylene, propyne, butyne, pentyne, and hexyne. Divalent aromatic groups include phenylene, biphenylene, alkylbenzene, dialkylbenzene, ynylbenzene, diynylbenzene, and naphthylene. Alkylene groups, olefins, and divalent aromatic groups are preferred, with ethylene and phenylene being particularly preferred.

[0062] The precursor can be manufactured by known methods. Hereinafter, preferred manufacturing methods are illustrated as (1), (2), and (3). However, the manufacturing methods are not limited to these.

[0063] (1) A method for producing a silane compound as a precursor, wherein one or more of the above-mentioned silane compounds having one or more substituents and one or more hydrolyzable groups are subjected to a hydrolysis-condensation reaction in an organic solvent in the presence of a catalyst, thereby producing a silane compound as a precursor.

[0064] When the hydrolyzable group is halogen, the preferred catalysts are catalyst-free, alkali metal hydroxides, and amines. For other hydrolyzable groups, acidic or basic catalysts can be used appropriately; as acidic catalysts, phosphoric acid, hydrochloric acid, sulfuric acid, and p-toluenesulfonic acid are preferred; as basic catalysts, amines, sodium hydroxide, and potassium hydroxide are preferred.

[0065] (2) A method for producing a silane compound as a precursor, wherein a siloxane compound having the above-mentioned substituents and hydroxysilyl groups is subjected to a siloxane reaction with a siloxane compound having the above-mentioned substituents and vinylsilyl or allylsilyl groups in an organic solvent by using a platinum catalyst such as platinum chloride or an organoplasmic complex, thereby producing a silane compound as a precursor.

[0066] (3) A method for producing a silane compound as a precursor, wherein a silane compound having the above-mentioned substituents and hydrolyzable groups, and a hydroxysilyl compound, and a silane compound having the above-mentioned substituents and hydrolyzable groups, and a vinylsilyl or allylsilyl compound, are subjected to a silylation reaction in an organic solvent by using a platinum catalyst such as platinum chloride or an organoplasmic complex, and then an acidic catalyst or a basic catalyst is used to form siloxane bonds for hydrolysis reaction, thereby producing a silane compound as a precursor.

[0067] The solvents mentioned above are preferably aromatics, alcohols, ketones, esters, aliphatic amines, aromatic amines, amides, nitriles, and thioethers. Particularly preferred solvents include toluene, xylene, ethanol, isopropanol, butanol, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, butyl acetate, trimethylamine, triethylamine, tributylamine, piperidine, pyridine, pyrrole, imidazole, dimethylformamide, dimethylacetamide, methylpyrrolidone, methylpyrrolidone, acetonitrile, and dimethyl sulfoxide.

[0068] (Free carbon F)

[0069] In the battery active material of the present invention, the amorphous silicon-based material has a SiOC framework structure and a framework portion composed only of carbon. A portion of the carbon atoms are bonded to a portion of the Si atoms in the SiOC framework, and this is called free carbon, which is a component that affects charge-discharge characteristics. Hereinafter, this free carbon is referred to as free carbon F. Free carbon F is formed in an aggregate of SiOC composed of SiO2C2, SiO3C, and SiO4, and is bonded to a portion of the Si atoms in the SiOC. Therefore, electron transfer between the Si atoms inside and on the surface of the SiOC and the free carbon F becomes easier. Thus, it can be considered that the insertion and removal reactions of lithium ions occur rapidly during charge and discharge, improving the charge-discharge characteristics of the SiOC active material. Furthermore, while the SiOC active material sometimes undergoes slight expansion and contraction due to the lithium ion insertion and removal reactions, the presence of free carbon F in its vicinity mitigates the overall expansion and contraction of the active material, resulting in a significant improvement in cycle characteristics.

[0070] The aforementioned free carbon F is formed during the thermal decomposition of the precursor silane compound in an inert gas atmosphere. Specifically, the free carbon F is characterized by the following: carbonizable sites and substituents present in the molecular structure of the silane compound undergo high-temperature thermal decomposition in an atmosphere that deactivates it, becoming carbon components. A portion of these carbons then combines with a portion of the SiOC skeleton. The aforementioned carbonizable components are not particularly limited, but are preferably hydrocarbons, more preferably alkyl, alkylene, olefin, alkyne, or aromatic compounds, and even more preferably aromatic compounds.

[0071] The amount of free carbon (F) is a crucial parameter for the charge-discharge characteristics of active materials. Insufficient carbon content can lead to poor conductivity and deteriorated charge-discharge characteristics. Conversely, excessive free carbon (F) results in a lower overall charge-discharge capacity of the active material due to the low theoretical capacity of the free carbon itself.

[0072] The state of free carbon F can be identified using thermogravimeter-differential thermal analysis (TG-DTA). Unlike the C atoms in the SiOC framework, free carbon F readily decomposes in the atmosphere, and the total amount of free carbon can be determined by the thermogravimetric loss measured in the presence of air. In other words, the total amount of free carbon can be quantified using a thermogravimeter-differential thermal analyzer (TG-DTA). Furthermore, changes in the thermal decomposition temperature behavior (decomposition reaction start temperature, decomposition reaction end temperature, number of thermal decomposition reaction species, temperature of maximum weight loss for each thermal decomposition reaction species, etc.) derived from this thermogravimetric loss behavior can be easily monitored, and these temperature values ​​can be used to determine the state of free carbon F. On the other hand, the C atoms in the SiOC framework, i.e., the carbon atoms bonded to the Si atoms constituting SiO2C2, SiO3C, and SiO4, are considered to have very strong chemical bonds, thus exhibiting high thermal stability and not decomposing in the atmosphere within the temperature range measured by the thermogravimeter. Furthermore, the free carbon F formed by the thermal decomposition of the aforementioned organosilanes in an inert gas atmosphere has properties similar to hard carbon. Therefore, a sharp weight loss occurs during thermal decomposition in the atmosphere at a temperature range of approximately 550°C to 900°C. There is no particular limitation on the maximum temperature for TG-DTA determination. However, to ensure complete completion of the thermal decomposition reaction of all free carbon, it is preferable to perform the TG-DTA determination in the atmosphere at a temperature ranging from room temperature (approximately 25°C) to above 1000°C.

[0073] When the active material for batteries of the present invention contains a certain amount or more of free carbon F, it is preferable that the starting temperature for the reduction of thermal weight during thermal decomposition of the active material in air is 550°C or higher. Furthermore, when containing free carbon F, for the reasons stated above, the amount of reduction in thermal weight is preferably 2 wt% or more and 30 wt% or less, more preferably 3 wt% or more and 25 wt% or less.

[0074] When the aforementioned active material contains free carbon (F), in addition to the thermal analysis methods described above, the state of the free carbon can also be determined by Raman spectroscopy. In Raman spectroscopy, the free carbon is located at 1590 cm⁻¹. -1 The nearby carbon D-band (graphite long-period carbon lattice structure) is located at 1350 cm⁻¹. -1 The peak intensity ratio G / D of the D band of nearby carbon (a disordered, defective short-period carbon lattice structure of graphite) is preferably 0.8 or less, more preferably 0.6 or more and 0.8 or less. If G / D is within this range, a state of balance is achieved between the long-period and short-period structures of free carbon, which can promote electron transfer between SiOC3, SiO2C2, SiO3C, and SiO4 and free carbon, and is therefore preferred.

[0075] <Composite Active Materials for Batteries>

[0076] The composite active material for batteries of the present invention is not particularly limited as long as it is included as part of the constituent elements. As a constituent element, it is preferable to further mix at least one carbon material selected from graphite, low-crystallinity carbon, and amorphous carbon, commonly used in battery anode materials, before or after firing. By including these various carbon materials, preferred characteristics can be exhibited based on their respective properties. For example, when composited with highly crystalline carbon materials such as graphite, it is preferable to improve the initial coulombic efficiency, cycle characteristics (lifetime), and capacity retention. The proportion of these carbon materials relative to the total amount of the composite active material is, for example, 1 to 80% by weight, preferably 5 to 60% by weight.

[0077] (Free carbon G)

[0078] The aforementioned carbon material, selected from graphite, low-crystallinity carbon, and amorphous carbon, possesses the properties described above and functions as a single carbon component, i.e., free carbon, in the active material. However, this free carbon does not have bonds with Si atoms in SiOC, unlike the free carbon described above in the context of free carbon F, where a portion of the carbon atoms are bonded to a portion of the Si atoms in SiOC, forming a tight bond with SiOC. Therefore, hereinafter, free carbon without bonds to Si atoms in SiOC will be referred to as free carbon G. Free carbon G improves the initial coulombic efficiency and capacity retention rate as described above due to the overall reduction in resistivity of the active material. However, compared to the characteristics of free carbon F described above, its effect on improving the charge-discharge characteristics of the SiOC active material is somewhat limited. Nevertheless, given the presence of free carbon F bonded to a portion of the Si atoms in SiOC, it is important to further combine free carbon G as a carbon component to further improve charge-discharge characteristics.

[0079] ((SiOC / carbon source resin / Si)3 component system)

[0080] The composite active material for batteries of the present invention is not particularly limited as long as it includes the active material for batteries of the present invention as part of its constituent elements. Preferably, it includes a carbon material as described above. As for the method of including the carbon material, besides the method of directly mixing the carbon material as described above, it can also be mixed and dispersed before firing to form a carbon source resin like the carbon material through firing. The carbon source resin is not particularly limited as long as it has good miscibility with polysiloxane compounds and is sometimes carbonized by high-temperature firing in an inactive atmosphere. Synthetic resins with aromatic functional groups, natural raw materials, etc., are preferred. Examples of synthetic resins include phenolic resins, polystyrene, polyphenylene ether, and polyphenylene sulfide. From the viewpoint of being inexpensive and eliminating impurities, phenolic resins are more preferred.

[0081] In the composite active material for batteries of the present invention, silicon (0-valent) particles with an average particle size [volume average particle size (D50)] of 150 nm or less may be included as a constituent element. By including such silicon particles, as described above, the initial charge-discharge performance (charge-discharge capacity, initial coulombic efficiency) of the active material is improved. The average particle size (D50) of the silicon particles is related to the cycling characteristics of the active material, and is therefore preferably 10 to 150 nm, more preferably 15 to 120 nm. The average particle size of the silicon particles can be measured by dynamic light scattering using a laser diffraction / scattering particle size distribution measuring device or the like. Large silicon particles larger than 150 nm form bulks, which easily cause micronization during charge-discharge, and therefore a tendency for the charge-discharge performance of the active material to decrease is expected. In addition, small silicon particles smaller than 10 nm are too fine, and therefore there is a tendency for silicon particles to easily aggregate. Therefore, it is difficult to uniformly disperse small silicon particles in the active material. In addition, due to the high surface activity energy of the tiny particles, the surface of the silicon particles is also easily oxidized. Furthermore, there is a tendency for byproducts to increase on the surface of the small silicon particles due to the high-temperature sintering of the active material, which will lead to a significant reduction in charge and discharge performance.

[0082] The shape of the silicon particles that may be included in the composite active material for batteries of the present invention is not particularly limited. As an example, a sheet shape is preferred. Furthermore, the length along the long axis is preferably 50 to 300 nm, and the thickness is preferably 1 to 60 nm. In the present invention, a sheet shape specifically refers to a thickness / length (so-called aspect ratio) of 0.5 or less. Large silicon particles with an aspect ratio exceeding 0.5 form bulky particles, which are prone to micronization during charging and discharging, and therefore a tendency for the charge-discharge performance of the active material to decrease is foreseeable.

[0083] The morphology of sheet-like silicon particles can be determined by measuring the average particle size using dynamic light scattering. Furthermore, the morphology (size, shape, etc.) of samples with the aforementioned thickness / length can be observed more easily and precisely using transmission electron microscopy (TEM) and field emission scanning electron microscopy (FE-SEM). It should be noted that in the case of negative electrode active material powder containing sheet-like silicon nanoparticles, the sample can be cut using a focused ion beam (FIB) or similar method to observe the cross-section using FE-SEM, or the sample can be sliced ​​and observed using TEM. The size range of silicon particles specified in this invention is a calculation based on 50 particles representing the main portion of the sample within the field of view shown in the TEM image. Since the field of view also has a limit, it is acceptable for the silicon particles in this invention to have sizes deviating from the aforementioned range. Additionally, silicon particles with a silicon purity of 97% or higher are preferred, and 99.0% or higher are more preferred.

[0084] As a constituent element of the composite active material for batteries of the present invention, when the carbon material and silicon particles described above are included, and the carbon material is contained in the precursor as a carbon source resin, it is preferable that, relative to the total weight of the precursor, the precursor contains 3 to 50% by mass of silicon particles, 15 to 85% by mass of silane compound solids, and the solids content of the carbon source resin is set to 3 to 70% by mass. More preferably, the amount of silicon particles is set to 8 to 40% by mass, the solids content of the silane compound is set to 20 to 70% by mass, and the solids content of the carbon source resin is set to 3 to 60% by mass.

[0085] (negative electrode)

[0086] In the secondary battery of the present invention, the negative electrode is obtained by coating a slurry, which is composed of the active material for batteries of the present invention or the composite active material for batteries of the present invention as an essential component and contains other organic binders (adhesives), conductive additives and other components as needed, onto the current collector copper foil to form a thin film.

[0087] Secondary batteries

[0088] There are no particular limitations on the secondary battery of the present invention as long as the negative electrode contains the battery active material or the battery composite active material of the present invention. The secondary battery of the present invention generally has the following structure: a wound electrode assembly is formed by winding the positive electrode, the aforementioned negative electrode, and a separator provided as needed into a flat spiral shape, or by stacking them into a flat plate shape to form a stacked electrode assembly, etc., and these electrode assemblies are sealed together with the electrolyte in an outer casing. For example, in the case of a wet electrolyte secondary battery, the secondary battery of the present invention can be constructed by arranging the positive electrode and the negative electrode of the present invention opposite each other across the separator and injecting electrolyte. By assembling the secondary battery according to this configuration, the secondary battery of the present invention can be manufactured.

[0089] The secondary battery of the present invention having such a negative electrode contains the battery active material of the present invention (or the battery composite active material of the present invention). Therefore, the negative electrode containing the battery active material of the present invention or the battery composite active material of the present invention can maintain good initial coulombic efficiency and cycle characteristics when used in a lithium-ion secondary battery, thereby increasing the discharge capacity to, for example, 800 mAh / g or more (half-cell measurement voltage range: 0.01-1.5V).

[0090] <Method for Manufacturing Active Materials for Batteries>

[0091] The active material for batteries of the present invention is not particularly limited. For example, when the above-mentioned silane compound is dissolved in an organic solvent, it can be manufactured by the following steps: a process of obtaining a precursor by desolventizing and drying the organic solvent (precursor manufacturing), a process of obtaining a calcined product by calcining the obtained precursor in an inactive atmosphere (precursor calcination), and a process of obtaining an active material by pulverizing the obtained calcined product (active material manufacturing).

[0092] (Precursor manufacturing)

[0093] In the process of obtaining the precursor described above, the organic solvent of the silane compound is desolventized and dried. For the desolventizing and drying operations aimed at removing the organic solvent by distillation, an apparatus equipped with a rotary evaporator, a heating section and a cooling section for removing glass or metal by reduced pressure or atmospheric pressure distillation, and components with heating, cooling, and pressure control functions can be used. For the drying operation, a hot air dryer, a reduced pressure dryer, or a spray dryer can be used.

[0094] As a component of the composite active material for batteries of the present invention, the process of mixing with the silane compound is required in the manufacturing of the precursor containing the aforementioned carbon material and silicon particles. However, any method can be used in this process, and this process can be performed either before or after solvent removal without any problem or particular limitation. Representative examples include dry and wet methods, but regardless of whether it is a dry or wet method, it can be carried out by stirring, oscillating mixing, vibration, flow stirring based on gas encapsulation, or various other methods. Various dispersion methods can be further used in the wet method. Representative examples include dispersers, homogenizers, ball mills, bead mills, FILMIX, and ultrasonic homogenizers. Furthermore, any dispersant or dispersion aid can be used, and in this case, the aforementioned dispersion methods can also be used.

[0095] (Addition of alkali metal compounds)

[0096] Alkali metal or alkaline earth metal compounds can also be added to the silane compounds of the aforementioned precursors. There are no particular limitations on the alkali metal or alkaline earth metal compounds; examples include lithium and magnesium metal compounds. Furthermore, alkali metal or alkaline earth metal compounds can also be added in the form of halogen compounds, organic complex compounds, etc. By mixing the aforementioned alkali metal or alkaline earth metal compounds with the aforementioned silane compounds, the irreversible electrochemical reactions present in the framework of the active material SiOC obtained through high-temperature calcination may sometimes react with or chemically combine with the alkali metal or alkaline earth metal compounds. Therefore, with the relative amount of irreversible reactions decreasing, an improvement in initial coulombic efficiency can be achieved.

[0097] (Firing of the precursor)

[0098] The aforementioned process for obtaining the calcined product involves calcining the aforementioned precursor at high temperature in an inactive atmosphere. Specifically, during the calcination of the precursor, the thermally decomposable organic components are completely decomposed, and other main components are precisely controlled under calcination conditions to obtain a calcined product suitable for the aforementioned active material or composite active material. More specifically, reactive activation sites such as free radical ends of Si, C, and O, and reactive coordination bonds are generated through the decomposition reaction of bonds such as Si-O and Si-C present in the aforementioned precursor silane compound. Furthermore, through the construction of newly generated Si-O and Si-C bonds by the reactions occurring at these reactive activation sites, a SiOC framework structure is formed. Moreover, in the case of a carbon source resin, the uniformly dispersed carbon source resin is also carbonized, thereby transforming into free carbon G within the three-dimensional structure having the SiOC framework.

[0099] (Firing conditions)

[0100] There are no particular restrictions on the firing conditions, but it is preferable to perform the process at approximately 600°C or higher in an inactive atmosphere. Firing is generally carried out by heating according to the program settings of the apparatus. The maximum temperature reached during firing is the set maximum temperature, which has a strong influence on the structure and properties of the fired product. The maximum temperature reached is preferably 1000°C to 1300°C, more preferably 1050°C to 1250°C. By firing within this temperature range, the chemical bonding state in amorphous silicon materials can be further refined, resulting in superior charge-discharge characteristics.

[0101] There are no particular limitations on the firing method; any reaction device with heating function can be used in an atmosphere. Continuous or batch methods can be employed. Regarding the firing equipment, fluidized bed reactors, rotary furnaces, vertical moving bed reactors, tunnel furnaces, batch furnaces, rotary kilns, etc., can be appropriately selected according to the purpose.

[0102] The firing process is preferably carried out in an atmosphere free of oxidizing gases, and more preferably in an inactive atmosphere such as nitrogen or argon, or in a nitrogen / hydrogen mixture, pure hydrogen, or a reducing atmosphere such as carbon monoxide.

[0103] (Pre-oxidation treatment)

[0104] Alternatively, a pre-oxidation treatment can be performed before the aforementioned precursor calcination. This pre-oxidation treatment not only allows for more efficient thermal decomposition of the organic components of the silane compound but also activates specific chemically bonded portions. Furthermore, in the case of silicon, a thin oxide film can be formed on the silicon surface. Additionally, when used in batteries, the chemical stability to the electrolyte is increased, preventing exposure of the silicon surface and inhibiting electrolyte decomposition. Therefore, by performing a pre-oxidation treatment, the cycle characteristics of the active material can be improved. Regarding the pre-oxidation treatment conditions, in atmospheric conditions, a temperature range of 200°C to 450°C is preferred, and 250°C to 400°C is more preferred.

[0105] (Manufacturing of active substances)

[0106] The process of obtaining active substances involves pulverizing the calcined material obtained above and classifying it as needed. Pulverization can be carried out in one stage to the target particle size or in multiple stages. For example, if the calcined material consists of lumps or agglomerated particles larger than 10 mm, and the goal is to produce 10 μm active substances, coarse pulverization is performed using a jaw crusher or roller crusher to produce particles of approximately 1 mm. These particles are then further pulverized to 100 μm using a mortar mill or ball mill, and finally pulverized to 10 μm using a bead mill or spray mill. Sometimes, the particles produced through pulverization contain coarse particles. To remove these, classification is performed while adjusting the particle size distribution by removing fine powder. The classifier used may be an air classifier or a wet classifier, depending on the purpose. However, sieving is preferred as it reliably achieves the goal of removing coarse particles.

[0107] <Method for manufacturing the negative electrode>

[0108] In the secondary battery of the present invention, the negative electrode is obtained by coating a slurry, which is composed of the battery active material or the battery composite active material of the present invention as essential components and contains other components such as organic binders (adhesives) and conductive additives as needed, onto a copper foil of a current collector to form a thin film. The negative electrode in the secondary battery of the present invention can be obtained, for example, by mixing the aforementioned battery active material or the battery composite active material of the present invention, and the binder as an organic binder, with a solvent using a dispersion device such as a mixer, ball mill, super mill, or pressure kneader to prepare a negative electrode material slurry, which is then coated onto a current collector to form a negative electrode layer. Alternatively, the paste-like negative electrode material slurry can be formed into sheet-like or granular shapes and integrated with the current collector.

[0109] (Organic adhesives: binders)

[0110] The aforementioned organic binders (adhesives) are not particularly limited, and examples include: styrene-butadiene rubber copolymers (SBR), (meth)acrylic acid copolymers formed from olefinic unsaturated carboxylic acid esters (e.g., methyl methacrylate, ethyl methacrylate, butyl methacrylate, methacrylonitrile, and hydroxyethyl methacrylate, etc.) and olefinic unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, etc.), and polymers such as polyvinylidene fluoride, polyethylene oxide, polyepoxychlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamide-imide, and carboxymethyl cellulose (CMC). Waterborne adhesives with high chemical stability can also be used as the aforementioned organic binders.

[0111] These organic binders (adhesives) are substances that are dispersed or dissolved in water, depending on their respective physical properties. Additionally, some are soluble in organic solvents such as N-methyl-2-pyrrolidone (NMP). The content of the organic binder in the negative electrode layer of the lithium-ion secondary battery is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, and even more preferably 3 to 15% by mass.

[0112] By ensuring the organic binder (adhesive) content is 1% by mass or more, good adhesion is achieved, and damage to the negative electrode structure caused by expansion and contraction during charging and discharging is suppressed. On the other hand, by ensuring the content is 30% by mass or less, the increase in electrode resistance is suppressed.

[0113] (Conductive additive)

[0114] In addition, conductive additives may be mixed into the aforementioned negative electrode material slurry as needed. Examples of conductive additives include carbon black, graphite, acetylene black, or oxides and nitrides that exhibit conductivity. The amount of conductive additive used is approximately 1 to 15% by mass relative to the total amount of the battery active material (or the battery composite active material of the present invention).

[0115] (Current collector)

[0116] There are no particular limitations on the material and shape of the current collector mentioned above. Strip current collectors made of copper, nickel, titanium, stainless steel, etc., in the form of foil, perforated foil, mesh, etc., can be used. In addition, porous materials, such as porous metals (foamed metals) and carbon paper, can also be used.

[0117] There are no particular limitations on the method for coating the aforementioned negative electrode material slurry onto the current collector. Examples of known methods include metal mask printing, electrostatic coating, dip coating, spraying, roller coating, doctor blade coating, gravure coating, and screen printing. After coating, it is preferable to perform calendering using a flatbed press, calendering rollers, or similar methods as needed. Furthermore, the integration of the negative electrode material slurry, which is formed into sheet or granular shapes, with the current collector can be achieved using known methods such as rollers, presses, or combinations thereof.

[0118] The negative electrode layer formed on the current collector and the negative electrode layer integrated with the current collector are preferably heat-treated according to the organic binder used. For example, when using a commonly known aqueous styrene-butadiene rubber copolymer (SBR), heat treatment at 100 to 130°C is sufficient; when using an organic binder with polyimide or polyamide-imide as the main skeleton, heat treatment at 150 to 450°C is preferred.

[0119] This heat treatment, through solvent removal and binder curing leading to increased strength, improves the adhesion between particles and between particles and the current collector. It should be noted that, to prevent oxidation of the current collector during the process, these heat treatments are preferably performed in inert atmospheres such as helium, argon, nitrogen, or a vacuum atmosphere.

[0120] Furthermore, after heat treatment, the negative electrode is preferably pre-pressed (pressure treated). In the negative electrode using the battery active material of the present invention (or the battery composite active material of the present invention), the electrode density is preferably 1.0 to 1.8 g / cm³. 3 More preferably, it is 1.1–1.7 g / cm³. 3 More preferably, it is 1.2–1.6 g / cm³. 3 Regarding electrode density, higher density tends to result in better sealing and higher volumetric density of the electrode. However, if the density is too high, the porosity in the electrode decreases, thereby weakening the suppression effect of volume expansion of silicon and other materials, and thus reducing cycle performance.

[0121] <Positive electrode>

[0122] The positive electrode described above can be obtained by forming a positive electrode layer on the surface of the current collector in the same way as the negative electrode described above. In this case, the current collector can be a strip current collector made of metals or alloys such as aluminum, titanium, and stainless steel in the form of foil, perforated foil, or mesh.

[0123] There are no particular restrictions on the positive electrode material used in the aforementioned positive electrode layer. In non-aqueous electrolyte secondary batteries, when manufacturing lithium-ion secondary batteries, any metal compound, metal oxide, metal sulfide, or conductive polymer material capable of doping or intercalating lithium ions can be used, without particular limitation. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCoxNiyMnzO2, x+y+z=1), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, and V6O2 can be used alone or in combination. 13 Conductive polymers such as VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), polyacetylene, polyaniline, polypyrrole, polythiophene, and porous carbon.

[0124] <Septum>

[0125] As the aforementioned separator, for example, nonwoven fabrics, cloths, microporous membranes, or combinations thereof with polyolefins such as polyethylene and polypropylene as the main components can be used. It should be noted that a separator is not required when the positive and negative electrodes of the manufactured non-aqueous electrolyte secondary battery are not in direct contact.

[0126] Electrolyte

[0127] As the electrolyte mentioned above, for example, an organic electrolyte can be used, in which lithium salts such as LiClO4, LiPF6, LiAsF6, LiBF4, and LiSO3CF3 are dissolved in a non-aqueous solvent such as ethylene carbonate, propylene carbonate, butyl carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, etc., or a mixture of two or more components.

[0128] Secondary batteries

[0129] The secondary battery of the present invention is not particularly limited and can be used as a paper-type battery, button-type battery, coin-type battery, stacked battery, cylindrical battery, prismatic battery, etc. The lithium-ion secondary battery negative electrode active material of the present invention can also be applied to all electrochemical devices that use lithium-ion insertion and removal as the charging and discharging mechanism, such as hybrid capacitors, solid lithium secondary batteries, etc.

[0130] Example

[0131] The following describes some representative examples of the actual production and evaluation of the active material for batteries of the present invention, but as mentioned above, the production and evaluation methods are not limited to these.

[0132] (Synthesis Example 1: Synthesis of Polysiloxane Precursors)

[0133] Using 21.8 g of trimethoxymethylsilane (MeSi(OMe)3) and 9.8 g of dimethoxydiphenylsilane (Ph2Si(OMe)2), a mixture of 34 g of isopropanol (IPA) was heated to 70 °C under a nitrogen atmosphere with stirring. After the temperature stabilized, 4.2 g of pure water and 0.17 g of a 1% phosphate ester IPA solution were added, and the reaction was allowed to proceed for 4 hours. The mixture was then heated to 130 °C, and the IPA and water were removed by distillation until they were completely eliminated, thus obtaining the polysiloxane precursor. The proportions (mol%) of each siloxane in the polysiloxane precursor are shown in Table 3.

[0134] (Synthesis Examples 2-7: Synthesis of Polysiloxane Precursors)

[0135] In Synthesis Example 1 above, trimethoxymethylsilane (MeSi(OMe)3) and dimethoxydiphenylsilane (Ph2Si(OMe)2) were replaced with trimethoxymethylsilane (MeSi(OMe)3), trimethoxyphenylsilane (PhSi(OMe)3), dimethoxydimethylsilane (Me2Si(OMe)2), and dimethoxydiphenylsilane (Ph2Si(OMe)2), respectively, and their respective weights were set to the values ​​recorded in Table 1. Otherwise, the process was identical to that of Synthesis Example 1. The proportions (mol%) of each siloxane in the polysiloxane precursor are shown in Table 3.

[0136] (Synthetic Examples 8-9: Synthesis of Precursors)

[0137] In Synthesis Example 1 above, the mixture of trimethoxymethylsilane (MeSi(OMe)3) and dimethoxydiphenylsilane (Ph2Si(OMe)2) and isopropanol (IPA) was replaced with polydimethylsiloxane (PDMS containing SiH), 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,4-bis(dimethylvinylsilyl)benzene, with the respective weights set to the values ​​shown in Table 2, and replaced with a mixture with 34 g of toluene. Otherwise, the process was identical to Synthesis Example 1. The proportions (mol%) of each siloxane in the polysiloxane precursor are shown in Table 3.

[0138] (Comparative Synthesis Examples 1 and 2: Synthesis of Polysiloxane Precursors)

[0139] In Synthesis Example 1 above, trimethoxymethylsilane (MeSi(OMe)3) and dimethoxydiphenylsilane (Ph2Si(OMe)2) were replaced with trimethoxymethylsilane (MeSi(OMe)3) and trimethoxyphenylsilane (PhSi(OMe)3), respectively, and their respective weights were set to the values ​​recorded in Table 2. Otherwise, the process was identical to Synthesis Example 1. The proportions (mol%) of each siloxane in the polysiloxane precursor are shown in Table 3.

[0140] (Comparative Synthesis Examples 3 and 4: Precursor Synthesis)

[0141] In Synthesis Example 8 above, the weights of the polydimethylsiloxane (PDMS containing SiH), 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,4-bis(dimethylvinylsilyl)benzene were set to the values ​​shown in Table 2. Otherwise, the process was carried out in the same manner as in Synthesis Example 8. The proportions (mol%) of each siloxane in the polysiloxane precursor are shown in Table 3.

[0142] [Table 1]

[0143]

[0144] [Table 2]

[0145]

[0146] (Examples 1-9, Comparative Examples 1-4: Preparation of active substances)

[0147] The precursors of the silane compounds obtained in Synthetic Examples 1-9 and Comparative Synthetic Examples 1-4 were calcined at 800°C for 2 hours under a nitrogen atmosphere, and then further calcined at 1100°C for 6 hours under a nitrogen atmosphere. After being pulverized in a mortar, they were further pulverized to about 5-10 μm using a bead mill to obtain the active substances.

[0148] (Example 10: Preparation of precursor complex and active substance)

[0149] In Synthesis Example 2, the reaction solution after the reaction was completed was distilled at 70°C under reduced pressure to remove IPA and water, and then concentrated until NV reached 60%. 30g of artificial graphite powder with an average particle size of 1 μm was added to 100g of this concentrate and dispersed using a disperser. Then, the solvent was completely distilled off at 110°C, and the solution was vacuum dried at 110°C to obtain a graphite-containing polysiloxane precursor.

[0150] The precursor was calcined at 800°C for 2 hours under a nitrogen atmosphere, and then further calcined at 1100°C for 6 hours under a nitrogen atmosphere. After being pulverized in a mortar, it was further pulverized to about 5-10 μm using a bead mill to obtain the various active substances.

[0151] (Example 11: Preparation of precursor complex and active substance)

[0152] In Example 10, 10g of commercially available Si particles with an average particle size of 100nm were added to a mixture made by adding 30g of graphite powder with an average particle size of 1 micrometer to 100g of the synthesized concentrate. Otherwise, all other steps were performed in the same manner as in Example 10.

[0153] (Comparative Example 5)

[0154] Instead of the reaction solution used in Synthesis Example 2 in Example 10, the reaction solution from Comparative Synthesis Example 3 after the reaction was completed was used. Otherwise, all procedures were carried out in the same manner as in Example 10.

[0155] (Comparative Example 6)

[0156] Instead of the reaction solution used in Synthesis Example 2 in Example 11, the reaction solution from the reaction of Comparative Synthesis Example 3 was used after the reaction was completed. Otherwise, all procedures were carried out in the same manner as in Example 11.

[0157] ( 29 (Measurement and Analytical Methods of Si-NMR)

[0158] Samples of each active substance from Examples 1-12 and Comparative Examples 1-6 were collected. In a solid-state NMR test tube, single-pulse measurements were performed using a solid-state NMR analyzer (JEOL RESONACE, JNM-ECA600). The obtained solid... 29 The Si-NMR spectral data were subjected to Fourier transform using Delta5, and waveform separation was performed on the obtained data using the Gauss+Lorentz function in ACD Labs software. Based on the peak areas obtained through waveform separation, the ratio (A / B) of the total integral value A of the peak values ​​attributed to SiOC3, SiO2C2, and SiO3C within the chemical shift range of 20ppm to -150ppm was calculated to the peak integral value B attributed to SiO4. The calculated A / B results are shown in Tables 4 and 5.

[0159] (Characteristic evaluation of active substances)

[0160] The samples of each active substance from Examples 1-12 and Comparative Examples 1-6 were heated to 1000°C in atmospheric atmosphere using a thermogravimetric differential thermal analysis (TG / TDA) device (model "Thermo plus EVO2", manufactured by RIGAKU). The temperature at which the weight began to decrease due to thermal decomposition was measured, and the rate of weight loss caused by this thermal decomposition was defined as the amount of free carbon. The thermal decomposition initiation temperature was determined from the measurement results. The amounts of free carbon are shown in Tables 4 and 5.

[0161] Furthermore, samples of each active substance from Examples 1-9 and Comparative Examples 1-4 were evaluated using Raman spectroscopy (model "NRS-5500", Japanese Spectrophotometer) at 1320 cm⁻¹. -1 The peak intensity D near (band D) is 1595 cm⁻¹ -1 The ratio of peak intensity G to D in the vicinity (G band). G / D is shown in Tables 4 and 5.

[0162] (Fabrication and evaluation of electrodes and batteries)

[0163] 800 mg of each active ingredient from Examples 1-11 and Comparative Examples 1-6, 100 mg of acetylene black (conductive additive), 25 mg of carboxymethyl cellulose, and 1000 mg of purified water were mixed and stirred at 2000 rpm for 5 minutes using AWATORI KENTARO, followed by degassing for 0.5 minutes. Then, 75 mg of styrene-butadiene rubber (adhesive) and 100 mg of purified water were added, and the mixture was further stirred at 2000 rpm for 5 minutes using AWATORI KENTARO, followed by degassing for 0.5 minutes to obtain a slurry.

[0164] The slurry was coated onto a copper plate with a film thickness of 60 μm and dried on a hot plate heated to 70°C for 5 minutes. Then, it was cut into circles with a diameter of 14 mm and dried under vacuum at 110°C to prepare the electrode as the negative electrode.

[0165] Using the negative electrode prepared as described above and the positive electrode as a Li metal foil, the negative electrode and the positive electrode are placed face to face with a 25 μm polypropylene membrane, and an electrolyte (1 mol / L LiPF6, diethyl carbonate: ethylene carbonate = 1:1 (volume ratio)) is adsorbed to prepare an evaluation half cell.

[0166] The charge-discharge characteristics were evaluated by performing 10 charge-discharge cycles under the following cutoff voltage and charge-discharge rate conditions. The initial efficiency and capacity retention (10 cycles) were calculated as follows. The evaluation results are shown in Tables 4 and 5.

[0167] Cut-off voltage range: 0.005~1.5V

[0168] Charge / discharge rates: 0.1C (from initial to 3 cycles), 0.2C (after 4 cycles)

[0169] Initial efficiency (%) = Initial discharge capacity (mAh / g) / Initial charge capacity (mAh / g)

[0170] Capacity retention rate (10th discharge) = Discharge capacity at the 10th discharge (mAh / g) / Initial discharge capacity (mAh / g)

[0171] [Table 3]

[0172]

[0173] [Table 4]

[0174]

[0175] [Table 5]

[0176]

Claims

1. A battery active material, comprising an amorphous silicon-based material containing Si, O, and C. In solid 29 Within the chemical shift range of 20 ppm to -150 ppm in Si-NMR spectra, the ratio A / B of the sum of the peak integrals attributed to SiO2C2 and SiO3C to the peak integral value attributed to SiO4 is greater than 0.5 and less than 5.

0. In the Raman spectrum of the active substance, it is located at 1595 cm⁻¹. -1 The nearby carbon G-band is located at 1320 cm⁻¹ -1 The peak intensity ratio of the D band of nearby carbon is above 0.6 and below 0.

75.

2. The active material for batteries according to claim 1, wherein, The weight reduction of the active substance during thermal decomposition in air begins at a temperature above 550°C.

3. The active material for batteries according to claim 1 or 2, wherein, The weight reduction of the active substance during thermal decomposition in air is more than 2 wt% and less than 30 wt%.

4. A secondary battery, wherein the negative electrode contains the active material as described in any one of claims 1 to 3.

5. A composite active material for batteries, comprising, as a part of its constituent elements, the active material according to any one of claims 1 to 3.

6. A composite active material for batteries, wherein the constituent elements of the composite active material according to claim 5 include at least one carbon material selected from graphite, low-crystallinity carbon, and amorphous carbon.

7. A composite active material for batteries, comprising silicon particles with an average particle size of less than 150 nm in the constituent elements of the composite active material according to claim 5 or 6.

8. A secondary battery, wherein the negative electrode contains the composite active material as described in any one of claims 5 to 7.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and active material manufacturing method

    JP1993144474A

  • Negative active material for nonaqueous electrolyte secondary battery, its manufacturing method, and nonaqueous electrolyte secondary battery

    JP2003197193A

  • Si-c-o-based composite and its manufacturing method as well as negative electrode material for non-aqueous electrolyte secondary battery

    JP2006062949A

  • Negative electrode and secondary battery equipped with the same

    JP2009283366A

  • Anode active material for secondary battery and method for producing the same, anode and lithium ion battery using the same

    CN107256957A